Implementasi kebijakan pengelolaan aset desa pada pasar Desa Sidorejo Kecamatan Pagelaran Kabupaten Malang - Fory Pacady; Agus Sholahuddin; Budhy Prianto (Universitas Merdeka Malang, 2020)
The purpose of this research is to describe and analyze the implementation of asset management policies in the market village of Sidorejo Village, Pagelaran District, Malang Regency based on Sidorejo Village Regulation Number 01 of 2009 and to analyze the factors that support and hinder the implementation of asset management policies in the market village of Sidorejo Village, Pagelaran Village, Malang Regency based on the Regulation Sidorejo Village Number 01 of 2009 concerning Village Market Management. The method used in this research is descriptive qualitative. The results of this study can be concluded that the implementation of Village Asset Management Policies at the Sidorejo Village Market, Pagelaran District, Malang Regency Based on the Sidorejo Village Regulation Number 01 of 2009 concerning Village Market Management in general can be said to be successful with the condition that there is a real impact from the policy output, namely the Village Head Regulation of Sidorejo Village Number. 4 of 2009.